Increase in vessel luminal diameter after rotational atherectomy: a study from multan institute of cardiology, pakistan - Momin Rasheed; Badar Ul Ahad Gill; M. Ikram Farid; Mubashir Sherwani; Muhammad Shahzad Fareed; Masood Ahmad Khan (Medical Journal of South Punjab, 2024)
Objective: To determine the increase in vessel luminal diameter in patients undergoing rotational atherectomy at Multan Institute of Cardiology, Pakistan. Material and Methods: A descriptive study enrolled 100 patients undergoing rotational atherectomy at Multan Institute of Cardiology, Pakistan. After baseline characteristics, the pre- and post-procedural minimal luminal diameter and reference vessel diameter were recorded. The change in luminal diameter was recorded in terms of mean and standard deviation. We stratified the data, applied a post-stratification t-test, and considered a p-value of less than 0.05 as significant. Results: The mean age was 52.20 ± 11.19 years, with more male (76.0%) patients. Risk factors included hypertension (45.0%), smoking (40.0%), diabetes (34.0%), and hyperlipidemia (32.0%). Lesions most frequently involved was the left anterior descending artery (LAD: 55.0%), with mid-distal location (65.0%) and severe calcification (71.0%). The minimal lumen diameter (MLD) significantly increased from pre-procedure and post-procedure 0.75?±?0.14?mm to 1.88?±?0.22?mm (p?<?0.001). At the same time, the mean luminal gain was 1.13±0.026?mm. The luminal gain with relation to reference diameter was 46%. Conclusion: Rotational atherectomy can lead to significant luminal gain with remarkable procedural success.